Distributed Wireless Measurement System for Transient Pressure with Data Extraction Technology - Wenlian Wang; Jinwen Zhang; Zhijie Zhang (International Journal of Distributed Sensor Networks)
Transient pressure measurement system applied in an explosion field is usually characterized by non-real-time measurement due to the conflict between quick signal acquisition and limited communication bandwidth. The correct signal acquisition is launched by triggering, but the false triggering often leads to measurement failure due to the fact that the operating status of system cannot be real-time detected in an explosion condition. A distributed wireless measurement system with data extraction technology is proposed in this paper to improve the reliability of transient pressure measurement. A long-time signal acquisition is achieved by mass data storage to eliminate the trigger mode. On the other hand, an effective data segment is extracted by signal identification, which improves the efficiency of data transmission and data processing. A measurement system based on data extraction technology was designed and implemented in an explosion field, and the measurement node was characterized by sampling rate of 1 Msps, data storage of 128 Gb, effective data segment of 512 kW, and Wi-Fi wireless network coverage.